Effect of a new type of high-strength lightweight foamed concrete on seismic performance of cold-formed steel shear walls. (30th August 2018) - Xu, Zhifeng; Chen, Zhongfan; Yang, Suhang
Highlights: A new type of HLFC with high bearing capacity and good thermal property is prepared. The effects of HLFC on seismic behavior of CFS shear wall are investigated. A simplified design formula is proposed to predicting shear strength of HLFC-filled CFS shear walls. Abstract: High-strength lightweight foamed concrete (HLFC), as a new type of load-bearing structural material, was developed using suitable mix proportion and physical method in this study. Material properties of HLFC with dry density of 500 kg/m 3 and 700 kg/m 3 were studied by a series of tests. To investigate the effect of HLFC on seismic behavior of cold-formed steel (CFS) shear walls, three shear wall specimens were fabricated and tested under in-plane cycle loading. The effects of HLFC on failure mode, load-bearing capacity, ductility, stiffness degradation and energy dissipation capacity of the walls were analyzed. Test results indicated that HLFC with density grade of A05 and A07 exhibit higher compressive strength and better thermal insulation than conventional foamed concrete. Furthermore, the compressive strength and thermal insulation of HLFC meets the requirements of both the load-bearing capacity and thermal insulation property of shear walls. Moreover, the use of HLFC in CFS shear wall changes failure mode of the walls from local failure to shear failure. Due to compressive strength of HLFC, restriction effect of HLFC on steel frame and bond-slip behavior between HLFC and studs, HLFC-filled CFS shear walls are superior to conventional CFS shear wall in terms of load-bearing capacity, ductility, stiffness and energy dissipation capacity. Finally, based on shear strength of the HLFC-filled CFS shear walls, the existing formula proposed by the standard CNS 383-16 is suitable for predicting the shear strength of HLFC-filled CFS shear walls, and the differences between the experimental and calculated results were within 10%.